Bentuk Dan Elemen Gerak Tari Dayang-Dayang - Hary Murcahyanto; Yuspianal Imtihan; Riyana Rizki Yuliatin; Hidriana Sulastri Mahyumi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This paper is based on the results of a study aimed at describing the forms of motions and elements of Dayang-dayang dance movements in Lombok Timur Regency. The form of motion in question is a form that is produced from the dancer's body language and the element of motion consists of space, time and energy used. Using a qualitative approach with a focus on the form of motion and the elements of Dayang-dayang dance moves. Data collection uses observation, interviews and study documents analyzed by reducing data, grouping, presenting and summarizing data. The result of this study concluded that the form of Dayang-dayang dance moves consisted of five forms of sedentary motion and three forms of movement while Dayang-dayang dance elements were dominated by upper, middle, and lower levels with slow rhythm toward diagonal, side and front. Keywords: Forms Of Motion, Elements Of Motion, Dayang-Dayang Dance.